Salvia ayecarrenoi (Lamiaceae), a new species with exserted stamens from Guerrero, Mexico - Martínez-Gordillo, Martha J.; de Santiago Gómez, Jesús Ricardo; Fragoso-Martínez, Itzi (Instituto de Ecología, A.C., 2023)
Background and Aims: During an expedition to Atoyac de Álvarez, a poorly explored region of Guerrero, specimens of Salvia with characteristics that are uncommon in Mexican taxa were collected. The aim of this work is to describe and illustrate Salvia ayecarrenoi and discuss its morphological affinities. Methods: Identification keys were employed to determine the collected specimens to sectional level. A morphological comparison with the taxa of the section Siphonantha was made using literature, herbaria collections and databases. The conservation state of the new species was determined based on the IUCN criteria. Key results: Salvia ayecarrenoi is a species endemic to Guerrero, with a unique character combination: inflorescences up to 46 cm long, violet-colored flowers, ventricose tube, exserted and curved stamens. The latter characteristic is common in South American species, but rare in Mexican taxa. Thus, its morphology is close to section Siphonantha, a group of five taxa from the Northern Andes. The new species shares some morphological characteristics with Salvia sigchosica. However, it differs from it mainly by the absence of nectar guides, the ventricose corolla tube, the cucullate lower lip of the corolla and the upper stigmatic branch well-developed and longer than the inferior branch. According to the IUCN criteria, the new species is Critically Endangered (CR B1a). Conclusions: With the description of Salvia ayecarrenoi, the number of Mexican species of Salvia subgenus Calosphace increases to 311. The morphological affinities of the new species place it in a South American section. However, other sections with disjunct distribution have resulted non-monophyletic. Thus, it is necessary to re-evaluate the infrageneric classification of the group and the morphological characters used to circumscribe sections, with the aim of achieving more natural groupings.